A method for determining the equivalent level of noise generated by a system of sources in an enclosure - MAKAREWICZ, Rufin; KERBER, Gabriela (Archives of Acoustics, 1982)
This paper proposes and subsequently verifies a method for determining the equivalent noise level Leg of noise in an enclosure. This method requires the identification of "elementary signals" related to single "acoustic events" and measurements permitting the calculation of numerical values of some parameters a_i for each of these signals. This methods permits the determination of the values of L_eq for any time interval when the value of a_i and the number of "elementary signals" reaching the observation point are known.